Investigation of Repeat Client Drop-Out and Re-Enrolment Cycles in Fourteen Methadone Maintenance Treatment Clinics in Guangdong, China - Zhang, Lei; Zou, Xia; Zhang, Di; Li, Xiaoling; Zhao, Peizhen; Ling, Li (PloS one, 2015)
Client adherence is vital for effective methadone maintenance treatment (MMT). This study explores the pattern and associated factors of client adherence, drop-out and re-enrolment in the Chinese MMT programme over the period of 2006-2013. This retrospective study was conducted in 14 MMT clinics in Guangdong Province, China. We employed Kaplan-Meier survival analysis to estimate the rates of drop-out and re-enrolment of MMT clients and multivariate Cox regression to identify associated factors. Among 1,512 study participants, 79% have experienced 'drop-out' during the 7-year study period. However, 82% 'dropped-out' clients resumed treatment at a later time. Low education level (junior high or below versus otherwise, HR = 1.21, 1.05-1.40), low methadone dosage in the first treatment episode (<50 ml versus ≥50 ml, HR = 1.84, 1.64-2.06) and higher proportion of positive urine test (≥50% versus<50%, HR = 3.72, 3.30-4.20) during the first treatment episode were strong predictors of subsequent drop-outs of the participants. Among the 'dropped-out' clients, being female (HR = 1.40, 1.23-1.60), being married (HR = 1.19, 1.09-1.30), and having a higher proportion of positive urine tests in the first treatment episode (≥50% versus<50%, HR = 1.35, 1.20-1.51) had greater likelihood of subsequent re-enrolment in MMT. Clients receiving lower methadone dosage (first treatment episode <50 ml versus ≥50 ml, HR = 1.12, 1.03-1.23; the last intake before drop-out <50 ml versus ≥50 ml, HR = 1.16, 1.04-1.30) were also more likely to re-enrol. Persistent cycling in-and-out of clients in MMT programmes is common. Insufficient dosage and higher proportion of positive urine samples in the first treatment episode are the key determinants for subsequent client drop-out and re-enrolment. Interventions should target clients in their early stage of treatment to improve retention in the long term.